Role of zootechnical additives on productivity and health of rabbits - Martínez, Y. (Cuban Journal of Agricultural Science, 2024)
In Latin America, subtherapeutic antibiotics are commonly used in the production of monogastric animals, although their use in rabbits is less relevant than in poultry and pigs. It is known that their use generates bacterial resistance, and they have proven harmful effects on human health. This review addresses the characterization and use of new nutraceutical additives, emphasizing phytobiotics, probiotics, and prebiotics and their effect on the biological indicators of rabbits in different productive categories. These natural alternatives have antimicrobial, anti-inflammatory, antioxidant, immunomodulatory and hypocholesterolemic effects, which can stimulate the native microbiota, the production of short-chain fatty acids and can provoke microbial eubiosis and, therefore, improve intestinal health, digestibility, productive efficiency and meat quality of rabbits. Also, they can alleviate the harmful effects of some common bacterial diseases and intoxications. However, the effectiveness of these natural alternatives will depend on the probiotic strain used, the main secondary metabolites in phytobiotics and the chemical structure of the prebiotics, as well as the health status, diet, age, and productive category of the rabbits.